Trichostatin A relieves anxiety-and depression-like symptoms in APP/PS1 mice - Su, Qiang; Ren, Yu-Hua; Liu, Guo-Wei; Gao, Yan-Ping; Zhang, Jiu-Xuan; Zhang, Jin-Nan; Pei, Xia-Xia; Li, Tian (Frontiers in Pharmacology, 2024)
Background: Cognitive deficits and behavioral disorders such as anxiety and depression are common manifestations of Alzheimer’s disease (AD). Our previous work demonstrated that Trichostatin A (TSA) could alleviate neuroinflammatory plaques and improve cognitive disorders. AD, anxiety, and depression are all associated with microglial inflammation. However, whether TSA could attenuate anxiety- and depression-like behaviors in APP/PS1 mice through anti-inflammatory signaling is still unclearly. Methods: In the present study, all mice were subjected to the open field, elevated plus maze, and forced swim tests to assess anxiety- and depression-related behaviors after TSA administration. To understand the possible mechanisms underlying the behavioral effects observed, CST7 was measured in the hippocampus of mice and LPS-treated BV2 microglia. Results: The results of this study indicated that TSA administration relieved the behaviors of depression and anxiety in APP/PS1 mice, and decreased CST7 levels in the hippocampus of APP/PS1 mice and LPS-induced BV2 cells. Conclusion: Overall, these findings support the idea that TSA might be beneficial for reducing neurobehavioral disorders in AD and this could be due to suppression of CST7-related microglial inflammation.